Better vegetable production systems in West Africa: prospects for the use of native antagonistic fungi for nematode management - Ahlé, V.; Coyne, Danny L.; Coosemans, J.; Affokpon, A.; Agbede, R.D. (2014)
Four isolates of the free-living antagonistic fungi Trichoderma asperellum T-12 (1012 spores/m2), Trichoderma brevicompactum T-3 (1012 spores/m2), Pochonia chlamydosporia Pc-1 (5×107 chamydospores/m2) and Paecilomyces sp. Pl-3 (1012 spores/m2), and two arbuscular mycorrhizal fungi, Kuklospora kentinensis M-233 (1000 spores/m2), Acaulospora scrobiculata M-353 (1000 spores/m2), all native to West Africa, were assessed for their root-knot nematode control potential on urban vegetable fields in the coastal area of Benin. The fungi were applied individually or in combination using a coconut husk carrier substrate, and were compared with the synthetic nematicide Furadan® (5 g/m2) under a double-cropping system of either tomato-carrot or carrot-lettuce, under farming conditions. Results were variable across sites; however, application of some native microorganisms alone or in combination resulted in significant suppression of nematode multiplication and root galling damage, improving crop yields and quality. Root galling severity on tomato and carrot was reduced by up to 70 and 30% in tomato-carrot cropping, and 16 and 40% on carrot and lettuce in carrot-lettuce cropping, respectively, compared to the Furadan treatment. Yields of tomato, carrot and lettuce were significantly improved by up to 70, 57 and 37%, respectively, following the application of various biocontrol agents. This study provides evidence that some beneficial microorganisms native to West Africa provide better protection for vegetables against root-knot nematode damage than the synthetic nematicides. This was observed especially in the poor sandy soils typical of urban and peri-urban sites of coastal cities in Benin, which reflect the situation in most West African countries. The results are highly encouraging, demonstrating the strong potential of the fungal isolates as an alternative to pesticides and a complementary crop protection component for the intensive (peri) urban vegetable systems.